Cardiac output: a central issue in patients with respiratory extracorporeal support. (January 2017) - Romagnoli, Stefano; Zagli, Giovanni; Ricci, Zaccaria; Villa, Gianluca; Barbani, Francesco; Pinelli, Fulvio; De Gaudio, Raffaele; Chelazzi, Cosimo
The iLA-activve ® Novalung is a new extracorporeal device specifically designed for lung support in patients with hypercapnic and/or hypoxemic respiratory failure. To date, only low-flow applications for decompensated hypercapnic chronic obstructive pulmonary disease have been reported in the literature. Here, we briefly report three cases of iLA-activve use in patients with hypercapnic-hypoxemic acute lung failure assisted with mid-flow (up to 2.4 L/min) and different single/double venous cannulation. The main findings of our small case series were: firstly, extracorporeal blood flows over 2.0 L/min across the membrane provided clinically satisfying decarboxylation and improved oxygenation; secondly, the ratio between blood flow through the membrane and the patient's cardiac output (CO) was a major determinant for the oxygen increase. The latter could, therefore, be a useful indicator for understanding performance in the complex and multifactorial evaluation of patients with extracorporeal veno-venous lung support.